Analysis of Teacher Self-Efficacy on Increasing Student’s Learning Motivation in Arabic Speaking Skill - Rochmat, Cecep Sobar; A’yun, Qurrotul; Ahmad Hidayatullah Zarkasyi; Zahirah, Sayyidah Aisyah (Jurnal Internasional Pendidikan Bahasa Arab, 2025)
Arabic has four skills necessary mandatory mastered by students, and Arabic speaking skill becomes the most prominent skill. In learning Arabic speaking skills, student needs motivation from the teacher to master this skill. However not all teacher has the ability to instill the motivation to learn. That's what makes the students feel the difficult in learning Arabic speaking skills. One of the teacher's abilities to finish the problem is high self-efficacy. Therefore, this research is intended to teacher self-efficacy and pragmatic to help the problems of learning Arabic skills. To see if teacher self-efficacy can play a role in learning Arabic speaking skills, this research was presented using descriptive qualitative methods. The data is collected by field survey on teacher self-efficacy during the learning process and listening method by listening to the teacher’s speaking during the learning process to obtain oral data. Based on research results, the majority of teachers struggle to improve their self-efficacy in terms of motivating students to learn Arabic speaking skills. Pragmatic studies can assess teacher’s words in motivating the students, because that’s what can influence student’s interest in learning Arabic speaking skill. The teacher improves their self-efficacy, not only through motivating students but also by improving their ability to organize the class while teaching.